Culture of Interculturality, Diversity, Equity, and Inclusion (IDEI) Assessment: Lessons from a Social Justice-Based Intercultural Learning Certificate Program for Preservice Teachers - Cherrel Miller Dyce; Katrice Hawthorne; Jamie Wire (MDPI AG, 2024)
Despite the pillars, rubrics, and standards provided by national education organizations and accrediting bodies, many educator preparation programs (EPPs) struggle to prepare teacher candidates to engage effectively with all children across differences in an intercultural context. The ability to engage across differences is especially important for teacher candidates as America's public schools are more diverse than ever. To increase teacher candidates' knowledge skills and dispositions, we propose a theory-based program focused on interculturality, diversity, equity, and inclusion (IDEI) that aligns with professional accreditation standards and weaves in effective assessment practices. By intentionally embedding assessment activities in program development, we hope to create a culture of IDEI assessment that not only meets accreditor standards but also results in program improvements and learners' development.